Destruction of Composite Materials and Structures - Kasym o va S.T; Talipova N.Z; Omonova D.F (Peerian Journals Publishing, 2022)
During operation, most structures operate under loads. This article presents the causes of the destruction of building structures, as well as the study of defects and damage. Information about the possibility of predicting the danger of destruction is given
Keywords: destruction; operation; structures; accelerated wear